Research progress in epidemiology and risk factors of thyroid cancer - ZHANG Zhiyue, HE Huijing, SHAN Guangliang, LIN Yansong (Zhongguo aizheng zazhi)
Thyroid cancer is the most common malignant tumor of the endocrine system and head and neck region, mainly including papillary thyroid cancer (PTC), follicular thyroid cancer (FTC), medullary thyroid cancer (MTC) and anaplastic thyroid cancer (ATC). Over the past few decades, the global incidence of thyroid cancer has risen rapidly, nearly doubling in some developed countries. Geographically, thyroid cancer incidence is higher in economically developed regions. Although the fastest increase in incidence has been observed in high-income countries, certain middle-income countries have also reported significant growth. Demographically, the incidence rate is notably higher in women than in men. In China, the incidence of thyroid cancer has increased significantly in recent years, while the mortality rate has remained stable at a low level. Urban areas report higher incidence rates than rural areas, and eastern coastal regions have higher rates compared to central and western regions. The etiology of thyroid cancer is multifaceted, with major risk factors including genetic predisposition, radiation exposure, iodine intake levels, endocrine disruptions, environmental and lifestyle factors. Among these, radiation exposure (particularly ionizing radiation during childhood) is a recognized critical risk factor. In addition, both insufficient and excessive iodine intake can disrupt thyroid function, thereby increasing disease risk. Genetic factors, such as familial clustering and gene (BRAF, RET/PTC, etc.) mutations, have been widely studied, while environmental pollution and modern lifestyles may also contribute to disease onset. Therefore, it is beneficial to conduct early screening for people with a family history of thyroid cancer, reduce unnecessary medical radiation exposure and conduct intervention on lifestyle-related risk factors such as obesity to prevent and control thyroid cancer. Most patients with thyroid cancer have a favorable prognosis. The main factors influencing the prognosis include pathological typing (PTC has a relatively better prognosis, while MTC and ATC have poorer prognoses), clinical staging (patients at TNM stages Ⅰ and Ⅱ have better prognoses, while those at stages Ⅲ and Ⅳ have worse ones), physiological factors (the overall prognosis of females is superior to that of males), genetic factors and environmental factors. Understanding the epidemiological trends and identifying factors influencing the onset and prognosis of thyroid cancer are essential for its prevention, treatment and health management. Future research should focus on identifying high-risk populations and developing targeted interventions to prevent and control thyroid cancer, reduce its disease burden, improve quality of life for patients, and lower healthcare costs.